SOX chemotherapy with anti-PD-1 and iNKT cell immunotherapies for stage IV gastric adenocarcinoma with liver metastases: A case report - Li, Dezhao; Liu, Mei; Wang, Jinhuan; Guo, Jia; Xu, Ningzhi; Lu, Jun (Frontiers in Immunology, 2022)
Gastric cancer (GC) is the fourth most common cancer worldwide, with overall 5-year survival rate of approximate 20%. Although multimodal treatments that combine surgery with chemotherapy and immunotherapy have been shown to improve survival, pathological complete response (pCR) is rare in advanced GC patients with liver metastases. Pre-clinical studies and clinical trials have demonstrated the antitumor efficacy of invariant natural killer T (iNKT) cells in various malignancies, including GC. While multimodal therapy comprised of chemotherapy, anti-programmed cell death-1 (PD-1) therapy, and iNKT cell immunotherapy have not been reported in GC patients. This case report describes the treatment of an early 60s patient diagnosed with advanced stage IVB (T1N1M1) adenocarcinomas of gastric cardia with liver metastases who received multimodal therapy comprised of SOX chemotherapy, anti-programmed cell death-1 (PD-1) therapy, and iNKT cell immunotherapy followed by surgical resection. Dramatic decreases in tumor area were observed in both the primary tumor and metastatic lesions following six cycles of SOX chemotherapy and iNKT cell immunotherapy, and four cycles of anti-PD-1 therapy. This combined treatment resulted in the transformation of a remarkably large, unresectable liver metastases into a resectable tumor, and the patient received total gastrectomy with D2 lymph node dissection and liver metastasectomy. Subsequent pathological examination detected no cancer cells in either the primary site or liver metastatic lesions, supporting the likelihood that this treatment achieved pCR. To our knowledge, this report represents the first case of a metastatic gastric cancer patient displaying pCR after six months of multimodal therapy, thus supporting that a SOX chemotherapy, anti-PD-1 therapy, and iNKT cell immunotherapy combination strategy may be effective for treating, and potentially curing, patients with advanced gastric adenocarcinoma.